STRATEGI HUMAS PEMERINTAH KABUPATEN SUMBAWA BARAT DALAM MENYAMPAIKAN INFORMASI KEPADA MASYARAKAT MELALUI SITUS WWW.SUMBAWABARATKAB.GO.ID - Yusmawati YMW (Jurnal Komunikasi, 2017)
Kabupaten Sumbawa Barat is located in NTB, is one of the areas that break away from its parent district according to the Autonomy Law Daerah. As a district that continues to grow, current and impartial information constantly about government policy, activity area, as well as access and agenda development area must be known by the local community. Public Relations is one of the important organs for local governments, because the Public Relations have a duty not only in terms of the formation of a positive image, also serves as a public relations communicator and also as a mediator for various purposes government agencies, as well as container and the voice of the people.This research is concerned about the Public Relations of Sumbawa Barat government strategy of local government in providing lighting and information to the public. Through this study, the authors wanted to describe how public relations strategy in disseminate of local government information to the public through new media. The research method used is descriptive qualitative, the authors obtain information by collecting all the data and the results are examined in the form of spoken words or relevant from a reliable source, and authors get an idea of the topics raised. The results of this study were conducted Public Relations of Sumbawa Barat government strategies in conveying information, namely the selection of new media as a means of communication in order to be able to touch all walks of life. A second strategy is the information content of diverse public relations website so that the public becomes aware of any information or good news regional news, national and international. And the third strategy is the process of delivering information that consists of multiple flow, so that the information provided is trustworthy and relevant and timely cultivated. Key word: Public relations strategy, providing information, internet